The Effects of CAR, LDR, NPL and OER on the Profitability of Digital Banks Listed on the Financial Services Authorities - Elisa Fitri; Ajeng Kartika Galuh (Contemporary Studies in Economic, Finance and Banking, 2025)
This research was conducted with the aim of determining the influence and relationship of the financial ratios CAR, LDR, NPL, and OER on the profitability of digital banks registered with the Financial Services Authority for the period 2018-2023. There are 15 digital banks that constitute the population in this study. The purposive sampling method was used as the sampling technique, so the sample used in this study consists of 7 digital banks with the largest assets. The type of research used is associative quantitative research with descriptive statistical methods. In this study, secondary data were used, obtained through financial reports downloaded from the official websites of each bank. This study provides results that CAR, LDR, NPL, and OER simultaneously affect the profitability of digital banks, but in partial tests, CAR, LDR, and NPL do not affect profitability, while OER has a negative and significant impact on the profitability of digital banks.